Mom's Parity Relationship with Fetus Death in Contents in Medan Sundari Hospital, 2019 - Fransiska Riati Nova Simbolon (Science Midwifery, 2020)
Intra-Uterine Fetal Death (IUFD/KJDK)is the occurrence of fetal death while still in the uterus that weighs 500 grams and or is 20 weeks or more gestational. The Government's effort to reduce maternal and fetal mortality is through the Making Pregnancy Safer (MPS) program. This program focuses on midwifery service efforts with a paradigm of preventing complications in health facilities. To prevent these complications, the midwife must know the factors that cause or predispose to an IUFD event in order to prevent or reduce the IUFD event factor. High parity (more than three) has a higher incidence of postpartum hemorrhage. The purpose of this study was to determine the relationship of parity with the occurrence of KJDK. Quantitative research methods are cross sectional. Based on the results of the study, the majority of respondents in the category of parity who are not at risk (<3) amounted to 19 respondents (61.3%) and risk categories (> 3) amounted to 12 respondents (11.1%). that out of 19 people who have risk parity there are 18 respondents (58.1%) experiencing KJDK, with a p-value = 0.001 which means greater than α-value (0.05). This means that there is significant relationship between parity and KJDK events in Sundari General Hospital in 2019.